Pengaruh Penggunaan Media Pembelajaran Vidio Terhadap Minat Belajar Siswa Kelas VII Pada Mata Pelajaran IPS Dalam Kurikulum Merdeka Di SMPN 5 Kota Solok - sari, anita putri; sari, yulia nita; syafwita, hani; setiawati, merika (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
The teaching and learning process that takes place makes students easily bored and tend not to be interested in learning using the Javanese Gegladhen Book or hearing Punokawan stories from teachers, because they cannot read and see directly the description of the Punokawan storyline, thus causing the non-achievement of learning objectives. Based on the background that has been found, the formulation of the problem can be obtained as follows: How is the feasibility of learning resources. CEKAWAN Book (Punokawan Stories) for Elementary School Students? How do teachers and students read the learning resources of the CEKAWAN Book (Punokawan Story) for Elementary School Students? This research approach includes Research and Development (RD) research. According to (Sugiyono, 2016), Research and Development (RD) is a research method used to produce a particular product and test the effectiveness of the product. This research aims to produce or develop products. The product developed in this study is a learning resource in the form of a CEKAWAN Book (Punokawan Story) for Elementary School Students.This research refers to the research and development design of modifications of the development model according to Borg and Gall. The result of the research and development of the resulting product is the cekawan (Punokawan Story) book for elementary school students. The results of the validation of the feasibility of assessment learning resources from 6 validators, Material experts 78.66%, Linguists 82.22%, and media experts 77.33% categorized as "FEASIBLE". The results of the readability trial of 10 students and 3 class teachers, class teachers 93.81%, students 97%, categorized as "FEASIBLE", and can be used as an additional learning resource for Javanese subjects in the Punokawan wayang story chapter.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengaruh penggunaan media pembelajaran video terhadap minat belajar siswa kelas VII pada mata pelajaran IPS dalam kurikulum merdeka di SMPN 5 Kota Solok. Media pembelajaran video berperan penting dalam minat belajar bagi kalangan peserta didik. Populasi penelitian ini merupakan siswa kelas VII di SMPN 5 Kota Solok. Dalam penelitian pengambilan sampel menggunakan teknik random sampling yang terdiri 53 sample. Alat pengumpulan data dalam penelitian ini menggunakan dua instrument yang pertama, Instrumen media pembelajaran video dan kedua minat belajar siswa. Analisis datanya menggunakan software SPSS version 22.0 hasil penelitian yang menunjukkan pada deskriptif pengaruh penggunaan media pembelajaran video secara keseluruhan adalah normal. Selain itu, analisis pada inferensi dengan analisis regresi menunjukkan hasil penelitian yang memberi pengaruh signifikan pada media pembelajaran video terhadap minat belajar dikalangan peserta didik yaitu 40%, maka dapat disimpulkan bahwa faktor pengaruh penggunaan media pembelajaran video terhadap minat belajar siswa di SMPN 5Kota Solok, berpengaruh secara signifikan.